Pengolahan Citra Digital pada Pembuatan Motif Keramik Menggunakan Grup Simetri - Steven Ray; Yessica Nataliani (Jurnal Buana Informatika, 2022)
Abstract. Digital Image Processing in Making Ceramic Patterns Using Symmetry Groups. The large number of requests for ceramic motifs makes ceramic craftsmen have to create a new and fast ceramic motif design idea. The generation of patterns on ceramic motifs digitally can be used by ceramic craftsmen. This study discusses the pattern of ceramic patterns using digital image processing with digital applications. The ceramic pattern design is made with a symmetrical pattern by the process of translation, rotation, reflection, and sliding reflection. The purpose of this research is to develop various ceramic patterns by applying symmetrical groups as motif designs on ceramics. The application is expected to make it easier for designers to find or create new designs from a basic pattern or what is commonly called a unit pattern or unit grid. The results obtained from this study are 17 patterns from 17 symmetric groups originating from one basic pattern. The combination of several patterns is also formed from the symmetry group into a new, more varied pattern.Keywords: Symmetric Group, Ceramic, Crystallography, Transformation. Abstrak. Banyaknya permintaan motif keramik membuat pengrajin keramik harus menciptakan sebuah ide desain motif keramik yang baru dan cepat. Pembangkitan pola pada motif keramik secara digital dapat digunakan oleh para pengrajin keramik. Penelitian ini membahas pola motif keramik menggunakan pengolahan citra digital dengan aplikasi digital. Desain motif keramik tersebut dibuat dengan pola simetris dari proses translasi, rotasi, refleksi, dan refleksi luncur. Tujuan penelitian ini adalah mengembangkan berbagai macam pola keramik dengan menerapkan grup simetris sebagai desain motif pada keramik. Aplikasi diharapkan dapat memudahkan para desainer untuk menemukan atau menciptakan desain-desain baru dari sebuah pola dasar atau yang biasa disebut pola satuan atau kisi satuan. Hasil yang didapat dari penelitian ini berupa 17 pola dari 17 grup simetri yang berasal dari satu pola dasar. Gabungan beberapa pola juga dibentuk dari grup simetri menjadi pola baru yang lebih bervariasi. Kata Kunci: Grup Simetris, Keramik, Kristalografi, Transformasi.